Effects of Seasonal Fire Applications on Northern Bobwhite Brood Habitat and Hunting Success - Leonard A. Brennan; Jeffrey M. Lee; Eric L. Staller; Shane D. Wellendorf; R. Shane Fuller (National Quail Symposium Proceedings, 2017)
Since the early part of the 20th century, land managers have used prescribed fire during February and March to maintain and enhance habitat for northern bobwhites (Colinus virginianus) in southern pine forests. During the past 2 decades, some managers have started to shift their use of fire to mimic more "natural" lightning-season (April to August) ignitions because these fires encourage flowering of plants in intact native ground cover, and are potentially more effective at hardwood control than winter fires. Therefore, we designed a short-term pilot study to evaluate whether seasonal applications of prescribed fire had any effect on bobwhite brood habitat (as measured by vegetation composition and arthropod biomass) or bobwhite abundance (as measured by hunting success) during the subsequent fall. During the first two years of our study (1994 and 1995), results showed that arthropod biomass and bobwhite hunting success were slightly greater on the shooting course burned during lightning-season (May) than the one burned during February and March. These results indicate that applications of lightning-season fire can be used, at least on a small scale (i.e., management blocks <250 ha) in southern pine forests for hardwood control, and possibly enhancement of native ground cover without short-term negative impacts on northern bobwhites.